DAMPAK PENGOPERASIAN JALAN TOL TRANS SUMATRA (JTTS) TERHADAP DINAMIKA PERTUMBUHAN EKONOMI PULAU SUMATRA - Putri, Rinaningtyas Anggriani; Firdaus, Ilham Pramadhitya (Jurnal Jalan Jembatan, 2025)
Toll road development is one of the key instruments for driving regional economic growth through increased connectivity and accessibility. The development of the Trans Sumatra Toll Road (JTTS) is a strategic effort in realising economic transformation on Sumatra Island. The transformation occurs due to a shift in the economic structure from the dominance of the primary sector to a more competitive one, resulting in greater economic and social benefits of development. This study aims to identify the impact of JTTS operations, including their implications for regional economic growth on Sumatra Island. The quantitative descriptive analysis method is employed, which involves analysing the economic profile, regional network, and economic growth, as well as conducting correlation analysis. The results of the study show that the regencies/cities crossed by JTTS experienced an average increase in gross regional domestic product (GRDP) of 1.28% and contributed 3.3% to the GRDP of Sumatra Island. The study found no significant relationship between economic growth and the JTTS length variable (correlation coefficient of 0.092) or road network density (correlation coefficient of 0.305). This finding suggests that the toll road network development strategy should still prioritise creating new connectivity between regions as the primary approach to developing regional infrastructure. Kata Kunci: jalan tol, pertumbuhan ekonomi, pengembangan wilayah, produk domestik regional bruto, Pulau Sumatra, analisis statistik deskriptif   Keywords: toll road, economic growth, regional development, gross regional domestic product, Sumatra Island, descriptive statistical analysis